Transexualismo: as decisões do Poder Judiciário no tocante à alteração do prenome a partir da Carta Cidadã de 1988 - Besso, Sandra (2011)
In the light of what was established by the 1988 Federal Constitution, fundamental rights began to be seen in a different way. Issues considered as complexes, however, such as transsexualism that according to the International Classification of Diseases (CID 10) is considered to be a 'Sexual Identity Disorder' and still raises deeper understanding from part of Society, the judiciary power, the executive power and the legislative power. The Brazilian Health System – SUS – has began allowing in Brazil the gender reassignment surgery, in which sexual reassignment is done, and legal criteria was therefore settled for this accomplishment. After surgery, however, comes a new problem: civil identity; because the person's new gender is not in line with his/her new civil register, causing him/her embarrassment. There is no law that regulates this matter at all. From this research observation, the present study aims to explore judicial decisions, from all states in the federation, by means of research in sites from respective courts, as well as high courts, seeking with terms as: 'transsexual' and 'first name'; using time filtering in the search, since 1988, which was the promulgation year of the Citizenship Letter, through the end of 2010. Having in view the lack of a law to regulate this issue, the primary scope here consisted in obtaining the narrative of how demands have been decided into this regard. The study conclusion suggests that although there is no established legal framework, the discourse of the judiciary power uses several arguments from the social, psychological and legal order, being properly, systematic and appreciated, as well as the legal principles, being in this case the principle of human person's dignity, as laid down in the Magna Carta, the most used one.